SOSIALISASI PENTINGNYA MENGONTROL ASUPAN GULA SEBAGAI PENCEGAHAN DIABETES MELITUS DI DUSUN CIHANDIWUNG LOR DESA ADIMULYA CILACAP - Nurdianti, Lusi; Febriani, Febriani; Irpan, Irpan; Irma, Irma; Iqbal, Iqbal; Nada, Nada; Rivia, Rivia; Yayang, Yayang (Jurnal Pengabdian Masyarakat (Jupemas), 2022)
This community service activity seeks early prevention related to diabetes by carrying out outreach about the importance of controlling daily sugar intake melitus in the Cihandiwung lor hamlet community, Adimulya village, Wamareja sub-district, Cilacap district. The method used is to provide health education in the form of lectures, discussions, and demonstrating the sugar content in each drink that is often found in the market. The level of awareness of respondents can be determined by carrying out a post test in the form of a questionnaire filled out by respondents to determine the level of awareness of respondents regarding the importance of controlling sugar intake as a way to prevent diabetes melitus from an early age. The post test was carried out after the counseling was given. Respondents' awareness of the importance of controlling sugar intake can be seen by looking at the post-test results that have been filled out by respondents after lectures and discussions. The output of this community service activity is a report that has been published in a journal and an increase in respondents' awareness about the importance of controlling sugar intake as an early prevention of diabetes melitus.